Information Technology Supplier Management in Hospitals - Indra Kharisma Raharjana; Ayundha Puspadini; Eva Hariyanti (Bulletin of Electrical Engineering and Informatics, 2018)
In this study, we developed a document for managing Information Technology suppliers in hospitals. This document is used to ensure the proper management of IT suppliers in the hospital. Products and services in Information Technology have characteristics and specifications that are always up to date, making it difficult for non-IT people to understand. Hospitals whose main business in the health sector is often lack of human resources who understand IT. Observations and interviews were conducted in Indonesian hospital, to identify the characteristics and problems in supplier management. Control Objectives for Information and Related Technologies (COBIT), Information Technology Infrastructure Library (ITIL) and government regulations on supplier management were reviewed and combined as a benchmark and guidance on how supplier management activities are carried out. The result of the process is a Standard Operating Procedure (SOP) document.    The parties involved in the supplier management process have evaluated the SOP document. From the results of the study, it is known that currently, the hospital is still focused on procedures procurement of goods and services that are government regulated. This study proposes some new activities that are not currently done by the hospital.